NIMG-03. PROSPECTIVE PHASE II RANDOMIZED TRIAL COMPARING PROTON THERAPY VS. PHOTON IMRT FOR GBM: SECONDARY ANALYSIS COMPARISON OF PROGRESSION FREE SURVIVAL BETWEEN RANO VS. CLINICAL AND RADIOLOGICAL ASSESSMENT. (11th November 2019) - Al Feghali, Karine; Randall, James; Wefel, Jeffrey; Guha-Thakurta, Nandita; Grosshans, David; Dibaj, Seyedeh; McAvoy, Sarah; Li, Jing; McGovern, Susan; McAleer, Mary; Ghia, Amol; Paulino, Arnold; et al.
Abstract: PURPOSE: To compare tumor progression based on clinical radiological assessment and on Response Assessment in Neuro-Oncology (RANO) criteria between GBM patients treated with proton radiotherapy (PT) vs. photon intensity modulated radiotherapy (IMRT). METHODS: Eligible patients were enrolled on the described prospective phase II trial and had MR imaging at baseline and follow-up beyond 12 weeks from treatment completion. 'Clinical' progression was based on a radiology report of progression in combination with changes in treatment due to suspected disease progression. A single blinded observer applied RANO criteria to determine the RANO-based tumor progression. RESULTS: Of 90 enrolled patients, 66 were evaluable, with median follow-up of 19.8 (Range: 3.2–65.1) months; median of 22.6 months for PT (n=25) vs. 18.9 months for IMRT (n=41). Median time to progression (TTP) was 7.9 months based on clinical progression criteria (8.1 months IMRT, 6.3 months PT) and 7.2 months (7.3 months IMRT, 5.7 months PT) by RANO criteria (p=ns for all). Median 'clinical' progression-free survival (PFS) was 8.7 (Range: 6.4–11.1) months; 8.9 months IMRT vs. 8.7 months PT (p=0.065). Median RANO PFS was 8.3 (range, 5.8–11.6) months: 8.3 months IMRT vs. 6.9 months PT (p=0.226). There were 14 discrepant cases: 3 had progression based on 'clinical' but not RANO criteria, and 11 had progression based on RANO but not 'clinical' criteria. CONCLUSION: Based on this secondary analysis of a randomized trial of PT vs. IMRT for GBM, there was no difference in tumor progression relative to treatment technique used. There was no statistical difference in PFS noted between clinical and RANO-based assessments, but RANO criteria identified progression more often than clinical assessment, and TTP was shortened with the use of RANO criteria alone. Further development of tumor assessment tools that improve consistency and accuracy of determining tumor progression are needed to guide therapeutic trials in GBM.